Предмет: Алгебра,
автор: ОгоньВода
Помогите решить показательное уравнение
9^(x+2)-26*3^(x+1)-3=0
Ответы
Автор ответа:
0
9 = 3²
9^(x + 2) - 26·3^(x+1) -3 = 0
9^x·9^2 -26·3^x·3^1 -3 = 0
3^x = t
81 t² - 78 t - 3 = 0
27 t² - 26 t -1 = 0
t = 1 t = -1/27
3^x= 1 3^x = -1/27(нет
x = 0
9^(x + 2) - 26·3^(x+1) -3 = 0
9^x·9^2 -26·3^x·3^1 -3 = 0
3^x = t
81 t² - 78 t - 3 = 0
27 t² - 26 t -1 = 0
t = 1 t = -1/27
3^x= 1 3^x = -1/27(нет
x = 0
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Математика,
автор: gamzinartem11
Предмет: Русский язык,
автор: Аноним
Предмет: География,
автор: Olsztyn
Предмет: Биология,
автор: джокермокер